7-Oxy-3,4-cyclohexenecoumarin Carrying Novel Zinc(II) and Indium(III) Acetate Phthalocyanines: Synthesis, Characterization, Photophysical and Photochemical Properties - YALÇIN, BAHATTİN; ÖZDEMİR, MÜCAHİT; SALAN, ÜMİT (WILEY-V C H VERLAG GMBH, 2019)
In this study, 7-hydroxy-3,4-cyclohexenecoumarin (1), two new phthalonitriles, 7-(2,3-dicyanophenoxy)-3,4-cyclohexene-coumarin (2), 7-(3,4-dicyanophenoxy)-3,4-cyclohexenecoumarin (3), were prepared. The phthalonitrile derivatives 2 and 3 were converted to the respective non-peripheral tetra, peripheral tetra 7-oxy-3,4-cyclohexenecoumarin substituted zinc(II) (4,6) and indium(III)acetate phthalocyanine (5,7) derivatives. All novel purified compounds (2-7) were characterized by elemental analysis, FT-IR, UV-vis, (HNMR)-H-1, 13CNMR, MALDI-TOF mass data. The spectral, photophysical (fluorescence quantum yields and lifetimes), and photochemical (singlet oxygen generation and photodegradation under light irradiation) properties of the synthesized Pcs (4-7) were studied in DMF, and the results were compared to determine the effects of the locations of substituents and the diversity of the central metal atom on these properties. The 7-oxy-3,4-cyclohexenecoumarin bearing phthalocyaninatozinc(II) and indium(III)acetate complexes showed good solubility in organic solvents such as chloroform, dichloromethane, tetrahydrofuran, acetone, DMF and DMSO. The fluorescence quenching behavior were investigated using 1,4-benzoquinone as a quencher. They have an acceptable level of singlet oxygen production, which determines the usability of phthalocyanines in photodynamic therapy applications and demonstrated appropriate photodegradation. The thermal properties of Pcs (4-7) were also investigated.
Keywords: Coumarin; DSC; PDT; Phthalocyanine; TGA; COUMARINS; DYES